Black Racial Stereotypes and Victim Blaming: Implications for Media Coverage and Criminal Proceedings in Cases of Police Violence against Racial and Ethnic Minorities. (4th December 2017) - Dukes, Kristin Nicole; Gaither, Sarah E.
Abstract: Posthumous stereotypical media portrayals of Michael Brown and other racial and ethnic minority victims of police violence have sparked questions about the influence of racial stereotypes on public opinions about their deaths and criminal proceedings for their killers. However, few studies have empirically investigated how the specific type of information released about a victim impacts opinions surrounding such incidents. Participants ( N = 453) read about an altercation that resulted in a shooting death where the race of the victim and shooter (Black vs. White) was randomly assigned. Participants learned either negative, Black male stereotypic or positive, Black male counterstereotypic information about the victim. Next, participants appraised levels of fault and blame, sympathy and empathy for the victim and shooter, and indictment recommendations for the shooter. Findings suggest that the type of information released about a victim can significantly sway attitudes toward the victim and the shooter. Implications for media portrayals of racial/ethnic minority victims of police violence and its impact on criminal sentencing are discussed.